A comparative investigation of the reduction of NO by CH4 on Pt, Pd, and Rh catalysts - Burch, Robbie; Ramli, Anita (1998)
Silica and alumina-supported Pd, Pt and Rh catalysts have been compared for the selective reduction of NO to N2 and the simultaneous oxidation of (2%. The results have demonstrated that the activities for the NO/CHd reaction do not follow the known trend in the activities of these metals for the oxidation of CH4 by 02. Under slightly fuel-rich conditions related to the composition of the exhaust gas from a natural gas engine, it is observed that Pt is the most active catalyst for the NO/CH4 reaction, being an order of magnitude more active than Pd and some 50 times more active than Rh. Significant support effects are also obtained with silica being the preferred support for Pt and Rh but alumina being better for Pd. It is proposed that the relative activities of the various catalysts reflect the ease of reduction of the catalysts by C& since it is thought that the conversion of NO to N2 involves the dissociation of NO on reduced surface sites. These active sites may be metal atoms, in the case of Pt, or oxygen anion vacancies, in the case of Pd and Rh. The formation of N20 is pronounced with Pt and Pd but absent with Rh. However, in all cases, substantial amounts of NH3 were observed at temperatures above 400°C. It is concluded that the optimum choice of catalyst for the simultaneous removal of NO and CH4 will depend on the gas composition and the temperature. Under fuel-rich conditions at moderate temperatures Pt is the most active catalyst for NO removal.